2014
DOI: 10.1371/journal.pgen.1004731
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Regulatory Systems Coordinate DNA Replication with Cell Growth in Bacillus subtilis

Abstract: In many bacteria the rate of DNA replication is linked with cellular physiology to ensure that genome duplication is coordinated with growth. Nutrient-mediated growth rate control of DNA replication initiation has been appreciated for decades, however the mechanism(s) that connects these cell cycle activities has eluded understanding. In order to help address this fundamental question we have investigated regulation of DNA replication in the model organism Bacillus subtilis. Contrary to the prevailing view we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
56
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(68 citation statements)
references
References 45 publications
11
56
0
Order By: Relevance
“…Moreover, the precise molecular mechanisms of how active DnaA accumulates in response to growth rate remain elusive. While it has been demonstrated that DnaA is the main factor governing replication frequency in E. coli, the situation seems to be slightly different in B. subtilis (Murray & Koh, 2014). Similar to E. coli, a reduction in DnaA abundance delayed DNA replication in fast-growing cells, which is consistent with a requirement for DnaA in driving frequent replication initiation.…”
Section: Coordination Of Dna Replication With Growth Ratementioning
confidence: 85%
“…Moreover, the precise molecular mechanisms of how active DnaA accumulates in response to growth rate remain elusive. While it has been demonstrated that DnaA is the main factor governing replication frequency in E. coli, the situation seems to be slightly different in B. subtilis (Murray & Koh, 2014). Similar to E. coli, a reduction in DnaA abundance delayed DNA replication in fast-growing cells, which is consistent with a requirement for DnaA in driving frequent replication initiation.…”
Section: Coordination Of Dna Replication With Growth Ratementioning
confidence: 85%
“…Recent work shows that specific ribosomal protein genes link cell growth to replication in Bacillus subtilis (60). We observed similar effects since S10 dosage correlated growth rate and oriC -firing frequency (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In the space allotted, we were barely able to scratch the surface of proteins predicted to act in similar ways to coordinate metabolism with regulation of cytoskeletal function or DNA replication (115)(116)(117)(118)(119). Based on the growing number of factors that appear to interact with MreB and/or FtsZ and have a seemingly unrelated enzymatic function, we would like to end with the following speculation: that at least some of the proteins proposed to have moonlighting functions may actually be utilizing interactions with FtsZ and MreB to localize their enzymatic activities to sites in the cell where their substrate is actively metabolized.…”
Section: Discussionmentioning
confidence: 99%